2021
DOI: 10.3389/fcvm.2021.702560
|View full text |Cite|
|
Sign up to set email alerts
|

Facts and Gaps in Exercise Influence on Arrhythmogenic Cardiomyopathy: New Insights From a Meta-Analysis Approach

Abstract: Arrhythmogenic cardiomyopathy (ACM) is a genetic cardiac condition characterized by fibrofatty myocardial replacement, either at the right ventricle, at the left ventricle, or with biventricular involvement. Ventricular arrhythmias and heart failure represent its main clinical features. Exercise benefits on mental and physical health are worldwide recognized. However, patients with ACM appear to be an exception. A thorough review of the literature was performed in PubMed searching for original papers with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This provides the anatomical substrate for ventricular tachycardias and ventricular fibrillation, as well as increased risk for sudden cardiac death [2]. The underlying genetic etiology is expanding with the identification of non-desmosomal targets such as intermediate filaments, ion channels and nuclear envelope proteins, although evidence on these variants is still emerging [1,3]. The presence of rapid-rate non-sustained ventricular tachycardia (RR-NSVT) predicts appropriate future implantable cardioverter-defibrillator (ICD) shocks, interpreted as a surrogate marker for sudden cardiac death [4].…”
Section: • Conscious Investigation On the Relationship Between Lifest...mentioning
confidence: 99%
See 1 more Smart Citation
“…This provides the anatomical substrate for ventricular tachycardias and ventricular fibrillation, as well as increased risk for sudden cardiac death [2]. The underlying genetic etiology is expanding with the identification of non-desmosomal targets such as intermediate filaments, ion channels and nuclear envelope proteins, although evidence on these variants is still emerging [1,3]. The presence of rapid-rate non-sustained ventricular tachycardia (RR-NSVT) predicts appropriate future implantable cardioverter-defibrillator (ICD) shocks, interpreted as a surrogate marker for sudden cardiac death [4].…”
Section: • Conscious Investigation On the Relationship Between Lifest...mentioning
confidence: 99%
“…2 The underlying genetic etiology is expanding with the identification of non-desmosomal targets such as intermediate filaments, ion channels and nuclear envelope proteins, although evidence on these variants is still emerging. 1,3 The presence of rapid-rate non-sustained ventricular tachycardia (RR-NSVT) predicts appropriate future implantable cardioverter-defibrillator (ICD) shocks, interpreted as a surrogate marker for sudden cardiac death. 4 Thus, RR-NSVT has been classified as an important risk factor for sudden cardiac death in AC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise exposure is known to be associated with a higher prevalence of an ACM-phenotype and VA in genotype positive family members of Gen-ACM probands ( 34 ) and clinical detraining was associated with a decrease in PVC burden in athletes with an ACM phenotype (whether Gen or ExI) ( 35 ). Continuation of exercise during the period between diagnosis and exercise testing therefore may worsen the clinical presentation, where refraining from exercise might result in a milder phenotype ( 36 ). Contrary to these findings, Costa et al ( 33 ) recently demonstrated that where non-adherence to the sports advice did associate with a decrease in physical capacity over time, there was no significant effect on VA or functional parameters.…”
Section: Limitationsmentioning
confidence: 99%
“…The prevalence of ARVC is estimated at 1:5000-1:1000. Notably, ARVC is a common cause of sudden death in young people, with some regional variability [10][11][12][13]. Disease diagnosis or manifestation is most common in the second to fifth decade of life, but children can also be affected by the disease [14][15][16].…”
Section: Introductionmentioning
confidence: 99%